Development of a multi-compartment pharmacokinetic model to characterize the exposure to Hexamoll® DINCH®. (June 2015) - Schütze, Andre; Lorber, Matthew; Gawrych, Katarzyna; Kolossa-Gehring, Marike; Apel, Petra; Brüning, Thomas; Koch, Holger M.
Highlights: We developed a descriptive multi-compartment model for 4 DINCH metabolites. The two-phase toxicokinetics are captured via a holding compartment. This 2-phase toxicokinetic delay mechanism is the key to DINCH PK modeling. The model can tie forward or backward exposure estimations to biomonitoring data. Abstract: We developed and calibrated a multi compartment pharmacokinetic (PK) model to predict urinary concentrations after oral exposure of four specific DINCH metabolites: MINCH, OH-MINCH, cx-MINCH, and oxo-MINCH. This descriptive model has 4 compartments: a "stomach" (SC) compartment, a "holding" (HC) compartment, a "blood" (BC) compartment and a "bladder" (BLC) compartment. DINCH is assumed to first deposit into the SC, with transfer split between the HC and the BC. Unmetabolized DINCH from the HC then transfers to the BC. The DINCH metabolism is assumed to occur in the BC before excretion via the BLC. At each urination event, all the metabolite mass in the BLC is excreted. The model was calibrated using published urine metabolite data from 3 different male volunteers, each orally dosed with 50 mg DINCH. Full urine voids were taken for 48 h after dosage. The predicted values showed a good agreement with the observed urinary DINCH metabolite concentrations, with a Spearman correlation coefficient exceeding 0.7 for all oxidized metabolites. We showed the importance of a holding reservoir. Without it, a good agreement could not be found. We applied the model to a set of 24-h general population samples measured for DINCH metabolites. The model was unable to duplicate the ratio of metabolites seen in the 24-h samples. Two possibilities were offered to explain the difference: the exposure pattern in the general population did not match the oral exposure in the dosing experiments, or the long-term toxicokinetics of DINCH was not captured in the 48-h controlled dosing experiments.